1999
DOI: 10.1034/j.1600-0420.1999.770614.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications after early surgery for congenital cataracts

Abstract: ABSTRACT.Purpose: To study the type and frequency of complications requiring additional surgery in infants operated on for congenital cataract before 12 months of age. Methods: The medical records of 57 infants who underwent surgery for unilateral and bilateral congenital cataracts during a five-year-period were reviewed retrospectively. The follow-up period ranged from 9 to 70 months with a mean of 37 months. Cataract extraction was performed on 83 eyes. Results: Thirty-eight operations for after-cataracts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 18 publications
3
50
0
7
Order By: Relevance
“…40 A Swedish study of infants undergoing cataract surgery before 12 months found that 10% developed glaucoma severe enough to require surgical intervention. 41 A bimodal onset of glaucoma was observed. An early onset group developed glaucoma within 6 months of surgery associated with angle closure.…”
Section: Complicationsmentioning
confidence: 98%
“…40 A Swedish study of infants undergoing cataract surgery before 12 months found that 10% developed glaucoma severe enough to require surgical intervention. 41 A bimodal onset of glaucoma was observed. An early onset group developed glaucoma within 6 months of surgery associated with angle closure.…”
Section: Complicationsmentioning
confidence: 98%
“…Essas complicações incluíam glaucoma de ângulo aberto ou por bloqueio pupilar, formação de membrana pupilar e corectopia (19)(20) . Além destas, duas outras complicações sabidamente conhecidas do implante de duas ou mais LIOs "piggyback" são: mudanças refracionais e formação de opacificações entre as lentes (13) .…”
Section: Discussionunclassified
“…Various studies have found glaucoma to be observed in 10-25% of children after paediatric cataract surgery. [68][69][70][71][72][73][74][75] Early age at surgery and presence of microphthalmia are high risk factors. Trivedi et al8 have found the incidence of glaucoma to be comparable between pseudophakic and aphakic eyes.…”
Section: Post-operative Complicationsmentioning
confidence: 99%